Some Aspects of the Behavior of Couplers in Color Photography (II): The irregular dye formation of some magenta couplers in color development - OGUCHI, Masanobu; SAKAMOTO, Kenro (The Journal of The Society of Scientific Photography of Japan, 1963)
It was found that when a photographic emulsion layer containing a certain diffusion-fast pyrazolone coupler is color processed, in certain cases the dye formation may not be complete. The phenomenon may be observed sometimes in the case of the processing by a mono-bath bleach-fixing solution containing the EDTA-FeIII complex as a oxidizing agent, but not in the processing by the combination of a ferricyanate bleaching solution and a fixing solution. Such an incompleteness of dye formation depends apparently upon the bleaching process, but it results from the midway stopping of dye formation merely in the color developing process. This irregular-dye-fromation can hardly be affected by the ordinary change of the sort of the developing agent and the quantity of sodium sulphite in the developing solution. It can also not be caused by various agents added to the emulsion, but depends upon the structure of couplers. The structure of couplers apt to show the phenomenon was made clear.